2007
DOI: 10.1007/s00586-007-0459-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a cervical disc prosthesis on maintaining sagittal alignment of the functional spinal unit and overall sagittal balance of the cervical spine

Abstract: The object of this study is to review the early clinical results and radiographic outcomes following insertion of the Bryan Cervical Disc Prosthesis (Medtronic Sofamor Danek, Memphis, TN), together with its effect on maintaining sagittal alignment of the functional spinal unit (FSU) and overall sagittal balance of the cervical spine for the treatment of single-level or two-level symptomatic disc disease. Forty-seven patients with symptomatic single or two-level cervical disc disease who received the Bryan Cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 32 publications
2
73
0
3
Order By: Relevance
“…Those reports investigated small number of cases and were largely cadaver studies or based on plain radiographs [3,4]. CT evaluation of bony structures is more accurate, and determination of lumbar endplate dimensions showed a large discrepancy to those of lumbar arthroplasty devices [20]. In the present trial, a surprisingly small percentage of endplates matched the endplate of the largest available disc prosthesis.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Those reports investigated small number of cases and were largely cadaver studies or based on plain radiographs [3,4]. CT evaluation of bony structures is more accurate, and determination of lumbar endplate dimensions showed a large discrepancy to those of lumbar arthroplasty devices [20]. In the present trial, a surprisingly small percentage of endplates matched the endplate of the largest available disc prosthesis.…”
Section: Discussionmentioning
confidence: 60%
“…It has already been reported that ideal footprint dimensions not only result in a significant reduction in subsidence, but also improve biomechanical loads [20]. Although subsidence of cervical disc devices , this kind of complication may increase with the imminent approval and widespread use of these devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively these findings suggest that the degree of lordotic curvature is a postural variable of the cervical spine which functions independently from the other angular measures that describe cranio-cervical posture. It is common practice to evaluate cervical lordosis as a clinical outcome measure following surgical intervention [8]. However, our results indicate that change in cervical lordosis is not significant and therefore it would be inappropriate to use this as a baseline measure for the changes likely to impact on the cervical spine, at least in opera singers.…”
Section: Discussionmentioning
confidence: 78%
“…Some studies reported that sagittal alignment in the cervical spine could be altered after TDR implantation [25][26][27][28]. This adverse effect was particularly noted after implantation of Bryan TM disc [26,28].…”
Section: Sagittal Alignmentmentioning
confidence: 99%